Keabsahan Tanda Tangan Narapidana Dalam Pembuatan Akta Jual Beli - Labibah, Hanin Alya'; Lestari, Arum Ayu (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
Legal subjects who are capable of doing legal acts making agreements are people who are adults and people who are not put under custody, there is a problem when one of the parties is a prisoner. The purpose of this study is to find out the prisoner's signature in the sale and purchase deed is valid or not according to civil law, as well as in the case that the sale and purchase deed signed by the prisoner has legal force or has no legal force. This type of research is normative legal research with a conceptual approach and a statutory approach. From this research, it can be concluded that the prisoner's signature in the sale and purchase deed is valid according to civil law in accordance with Article 3 of the Civil Code, namely that no punishment results in civil death, or loss of all citizenship rights, so that the prisoner has no legal action that can eliminate his civil rights including the signing of the sale and purchase deed. In the event that the legal force of the sale and purchase deed signed by the prisoner meets the element of misappropriation (misbruik van omstandigheiden), then the sale and purchase deed is declared invalid.